Web Services Quality Assurance: A XML-Based Quality Model - Dias Jr., José Jorge L.; da Cunha, José Adson O. G.; Álvaro, Alexandre; de Barros, Roberto S. M.; Meira, Silvio Romero de Lemos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2007: Anais do VI Simpósio Brasileiro de Qualidade de Software, 2007)
The task of reusing Web services that meet quality attributes requirements is a challenging issue in service-based development approach. In such a context, a quality model can provide the means to effectively evaluation of services, enabling the certification of these services. In this sense, this paper proposes a quality model based on the ISO 9126 standard, defining a set of attributes and metrics for an effective evaluation of Web services. A XML-based representation and security schema for the model was created to support a service certification process. Moreover, a preliminary case study was elaborate in order to verify the gap between the proposed model and the available information by the Web services providers.